Soluble TNFα blockade overcomes lapatinib resistance and induces an innate immune response in HER2-positive breast cancer - Bruni, Sofia (2020)
Lapatinib (LAP), a dual EGFR/HER2 tyrosine kinase inhibitor, is used as second-line therapy in women with HER2+ breast cancer (BC), but less than 25% of the patients achieve an objective response. An alternative therapeutic approach is needed to overcome LAP resistance in women with metastatic HER2+ BC, particularly in patients with central nervous system (CNS) metastasis where large biological molecules are not effective.